Association of the CYP3A4 Gene(rs2740574 C>A, G, T) with the Risk of Benign Prostatic Hyperplasia in Iraqi Patients (Medical Forum Monthly, 2025)
Objective: To evaluate the association between the genetic polymorphism rs2740574 in the CYP3A4 gene and the risk of developing benign prostatic hyperplasia in a sample of Iraqi patients.Study Design: Descriptive studyPlace and Duration of Study: This study was conducted at the Baqubah Teaching Hospital, Diyala Province, Iraq from October 2023 and May 2024.Methods: This descriptive study included 30 benign prostatic hyperplasia patients and 10 healthy controls aged between 50 and 70 years. DNA was extracted from the samples, and the target fragment was amplified usingpolymerase chain reaction. Genetic variations were analyzed using the Geneious software. The sequencing analysis of the rs2740574 polymorphism in the CYP3A4 gene revealed three genotypes: CC, CT, and TT.Results: A strong association between the genotype distribution of this polymorphism and the risk of BPH. The CC genotype and C allele were highly prevalent among the control group and represented a strong protective factor against BPH, supported by Fisher’s exact test (P=0.000) and an odds ratio (OR) of 0.003. In contrast, the CT genotype was significantly more frequent in patients and indicated a very high risk of disease (P=0.000, OR=81.00). The T allele was present in 51.67% of patients versus only 5% in controls, making it a major risk factor with an ORof 20.31. The TT genotype was rare and not statistically significant but was still considered a potential risk factor according to Fisher’s test (P=0.721) and OR=1.84. The Hardy–Weinberg equilibrium test showed genetic balance in the control group (P = 0.8678, not significant), indicating a normal distribution unaffected by disease pressure. However, the patient group showed a clear deviation from equilibrium (P=0.000), reflecting the influence of the disease state on genotype distribution in this sample.Conclusion: The genetic polymorphism of the rs2740574 of the gene could lead to the incidence of autism. A case of benign is that CYP3A4 gene has a huge role in genetic predisposition to benign. Women: prostatic hyperplasia.